THE HABITANTS OF PRECARPATHIA WHICH WERE ACTUAL AND ORDINARY MEMBERS NTSH (1873-1989) - Арсенич, П. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
On the basis of study of literature and archived sources short biographic information is given in alphabetical order about actual and ordinary members of NTSH, which were born or worked to 1939 year on territory of Ivano-Frankivsk region. Biographic references of natives of the edge which became members of NTSH out of the borders of Ukraine to 1989 are also included to the list.